Antenatal Allopurinol Reduces Hippocampal Brain Damage After Acute Birth Asphyxia in Late Gestation Fetal Sheep. (February 2014) - Kaandorp, Joepe J.; Derks, Jan B.; Oudijk, Martijn A.; Torrance, Helen L.; Harmsen, Marline G.; Nikkels, Peter G. J.; Bel, Frank van; Visser, Gerard H. A.; Giussani, Dino A.
Free radical–induced reperfusion injury is a recognized cause of brain damage in the newborn after birth asphyxia. The xanthine oxidase inhibitor allopurinol reduces free radical synthesis and crosses the placenta easily. Therefore, allopurinol is a promising therapeutic candidate. This study tested the hypothesis that maternal treatment with allopurinol during fetal asphyxia limits ischemia–reperfusion (I/R) damage to the fetal brain in ovine pregnancy. The I/R challenge was induced by 5 repeated measured compressions of the umbilical cord, each lasting 10 minutes, in chronically instrumented fetal sheep at 0.8 of gestation. Relative to control fetal brains, the I/R challenge induced significant neuronal damage in the fetal hippocampal cornu ammonis zones 3 and 4. Maternal treatment with allopurinol during the I/R challenge restored the fetal neuronal damage toward control scores. Maternal treatment with allopurinol offers potential neuroprotection to the fetal brain in the clinical management of perinatal asphyxia.